Evaluating public posting, goal setting, and rewards to increase physical activity in children. (4th August 2022) - Miller, Bryon G.; Livingston, Cynthia P.; Zerger, Heather M.; Valbuena, Diego A.; Miltenberger, Raymond G.
Abstract: In this study, we evaluated several components of a pedometer‐based intervention with children in an elementary‐school‐aged classroom, across 24‐h sessions. The intervention included combinations of self‐monitoring, goal setting, feedback, and reinforcement, and data were analyzed at both the classroom level (i.e., average daily step totals) and the individual level (i.e., daily step totals), across phases. The highest levels of physical activity were observed when components of self‐monitoring, public posting, goal setting, and feedback with reward were applied concurrently.